2022
DOI: 10.1007/s11301-022-00299-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on knowledge management in SMEs: current trends and future directions

Abstract: It is generally known that small and medium-sized enterprises (SMEs) are a significant driver of employment and economic growth for the majority of world economies. At the same time, SMEs are more fragile in times of crisis which in turn restricts their possibilities for action. In such an environment, it appears even more relevant for SMEs to consider knowledge and its management. Given that, it seems relevant to have an in-depth understanding of knowledge management (KM) in SMEs so that it can be better prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 87 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…RC is an important asset for enterprises with limited resources (Paoloni & Modaffari, 2022). In particular, SMEs rely on RC to enhance their internal innovation capabilities (Durst et al, 2022). Al-Jabri & Al-Busaidi (2018) have shown that knowledge transfer from outside the organization enhances internal learning because when external knowledge is acquired, it is often new and unknown to employees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RC is an important asset for enterprises with limited resources (Paoloni & Modaffari, 2022). In particular, SMEs rely on RC to enhance their internal innovation capabilities (Durst et al, 2022). Al-Jabri & Al-Busaidi (2018) have shown that knowledge transfer from outside the organization enhances internal learning because when external knowledge is acquired, it is often new and unknown to employees.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of large enterprises, effective KM positively influences organizational competitiveness and innovation leading to improved organizational performance (OP) (Torabia & El-Den, 2017). However, KM in SMEs is still a new research area (Kurniawati et al, 2019;Durst et al, 2022). In particular, KM that combines both knowledge inside and outside the enterprise has not yet been discovered (Durst et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, the large majority of KIBS companies have a small or medium size and they face obstacles to managing knowledge, in part due to their limited resources, in part to the knowledge-intensive and intangible nature of their business processes and outputs. Research on KM in SMEs in general and KIBS in particular (Siahtiri et al, 2020;Durst et al, 2022;Zbuchea et al, 2023;Massaro et al, 2016;Shekhar & Valeri, 2023) suggests that these firms face different issues and often lack both dedicated approaches to KM and the necessary skills as well as competencies necessary to implement proper knowledge management (KM) processes. At the same time, these firms are exposed, more than others, to skill shortage and to risk related to environmental change, progressive digitalization, and increasing geopolitical risks.…”
Section: Km Challenges and Processesmentioning
confidence: 99%
“…The large majority of KIBS companies have a small and medium size (Zieba, 2021) and, while empirical evidence (Bolisani et al, 2022) proves that they are aware that knowledge is their most crucial resource, they manage it in a substantially informal and undeliberate way (Bolisani et al, 2016;Alexandru et al, 2020). In general small companies face several issues in knowledge management (Massaro et al, 2016;Durst et al, 2022;Shekhar & Valeri, 2023), largely due to their limited size which results in scarcity of human and financial resources, lack of time, and shortterm orientation. In the specific case of KIBS, they can encounter specific challenges, mainly due to the intangible and knowledge-intensive nature of their business processes and outcomes.…”
Section: Introductionmentioning
confidence: 99%